Surgical Techniques and Long-term Outcomes of Living-donor Liver Transplantation With Inferior Vena Cava Replacement Using Atriocaval Synthetic Interposition Graft for Budd-Chiari Syndrome. Issue 4 (April 2019) - Yoon, Young-In; Lee, Sung-Gyu; Moon, Deok-Bog; Ahn, Chul-Soo; Hwang, Shin; Kim, Ki-Hun; Ha, Tae-Yong; Song, Gi-Won; Jung, Dong-Hwan; Park, Gil-Chun; Kim, Dong-Sik; Choo, Suk-Jung
Abstract : Objective: We aimed to describe our living-donor liver transplantation (LDLT) surgical technique and its long-term patency for patients with Budd-Chiari syndrome (BCS) and retrohepatic inferior vena cava (IVC) obstruction that extends up to the atrium. Background: From a technical perspective, LDLT for BCS with an IVC obstruction up to the right atrium is one of the most challenging surgical procedures. Consequently, the optimal surgical technique for patients with BCS has not yet been elucidated. Methods: A durable LDLT technique without piggy-back hepatectomy was designed using a large-caliber synthetic interposition vascular graft between the right atrium and the infrahepatic IVC for reconstructing the hepatic outflow tract in patients with BCS. Results: Between May 2006 and May 2017, 5 of 17 BCS patients who underwent LDLT required the described technique. All patients with a median follow-up of 10.5 years (range, 9.2–11.5 years) demonstrated the patent IVC grafts and no recurrence of BCS. Conclusions: Our refined technique does not require unnecessary and dangerous dissection of the diseased IVC, and eliminates the residual suprahepatic vena cava with the possibility of BCS recurrence by connecting the graft to the healthy atrium. Abstract : Supplemental Digital Content is available in the text